Lymph node tissue kallikrein-related peptidase 6 mRNA: a progression marker for colorectal cancer - Ohlsson, L (Nature Publishing Group, 2012)
BACKGROUND: A most important characteristic feature for poor prognosis in colorectal cancer (CRC) is the presence of lymph node metastasis. Determination of carcinoembryonic antigen (CEA) mRNA levels in lymph nodes has proven powerful for quantification of disseminated tumour cells. Here, we investigate the utility of human tissue kallikrein-related peptidase 6 (KLK6) mRNA as a progression biomarker to complement CEA mRNA, for improved selection of patients in need of adjuvant therapy and intensified follow-up after surgery. METHODS: Lymph nodes of pTNM stage I-IV CRC- (166 patients/503 lymph nodes) and control (23/108) patients were collected at surgery and analysed by quantitative RT–PCR. RESULTS: Lymph node KLK6 positivity was an indicator of poor outcome (hazard ratio 3.7). Risk of recurrence and cancer death increased with KLK6 lymph node levels. Patients with KLK6 lymph node levels above the 90th percentile had a hazard ratio of 6.5 and 76 months shorter average survival time compared to patients with KLK6 negative nodes. The KLK6 positivity in lymph nodes with few tumour cells, that is, low CEA mRNA levels, also indicated poor prognosis (hazard ratio 2.8). CONCLUSION: In CRC patients, lymph node KLK6 positivity indicated presence of aggressive tumour cells associated with poor prognosis and high risk of tumour recurrence.